AN ANALYSIS CODE SWITCHING IN INSTAGRAM - Deria Yunalizza, Dara; Putri, Manisa Laksana; Pratama, Muhammad Fatur Rizki; Prayoga, Giri; Cindiyana, Dhea Aura (Universitas Muhammadiyah Muara Bungo, 2024)
This article aims to examine the use of Indonesian to English code switching in the Instagram application which focuses on explaining in more detail the conversations being conveyed.